2007
DOI: 10.1108/09684880710748929
|View full text |Cite
|
Sign up to set email alerts
|

Admission requirements for transfer and non‐transfer students: should one size fit all?

Abstract: PurposeTo examine the efficacy of admission requirements as predictors of academic success in core business coursework, and as a rationing mechanism for limited course capacity, for both transfer and non‐transfer students following integration of the core business curriculum.Design/methodology/approachRegression analysis is used to test the efficacy of admission standards in explaining transfer and non‐transfer student performance in the core business curriculum, before and after substantial curricular revisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Nonetheless, this study has shown that these TS still managed to handle the multiple sources of workload and even demonstrated the abilities to develop active and independent learning while aiming for timely degree attainment. Regardless of their academic achievement, they seemed to have magnified their negative pre-transfer experiences and ignored that they were successful CC graduates who were retained in the highly competitive environment, still persisting with their baccalaureate studies [ 61 ]. TS’ self-stigmatization, as indicated by our findings, show that intervention is needed to rectify their self-perceptions.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, this study has shown that these TS still managed to handle the multiple sources of workload and even demonstrated the abilities to develop active and independent learning while aiming for timely degree attainment. Regardless of their academic achievement, they seemed to have magnified their negative pre-transfer experiences and ignored that they were successful CC graduates who were retained in the highly competitive environment, still persisting with their baccalaureate studies [ 61 ]. TS’ self-stigmatization, as indicated by our findings, show that intervention is needed to rectify their self-perceptions.…”
Section: Discussionmentioning
confidence: 99%
“…This research can be divided into two types of predictors: ability or cognitive measures and noncognitive measures. Historically, cognitive variables relevant to academic success (e.g., grade point average [GPA], the Scholastic Assessment Test (SAT), and the American College Test [ACT]) were presumed as accurate appraisals (Cohn, Cohn, Balch, & Bradley, 2004;Kobrin, Patterson, Shaw, Mattern, & Barbuti, 2008;Pharr & Lawrence, 2007). Further, Popham (2006) noted the significance the test scores have on the typical high school students as it is common practice to remember the scores long after the tests are taken as if students are branded by the test results.…”
Section: Literature Review and Conceptual Frameworkmentioning
confidence: 99%
“…In any institution, the goal of an admission office is to admit students who they believe will be successful at the institution they represent. Pharr and Lawrence (2007) questioned if transfer students and high school students should be held to the same admission standards. Similarly, Kopko and Crosta (2016) questioned if transfer students should be required to complete an associate degree before applying for admission to transfer to a four-year institution.…”
Section: The Admission and Enrollment Decision Process Can Look Much ...mentioning
confidence: 99%